Islamic ethics of business: a Maqāṣidic analysis - Muhammad Amanullah, Muhammad Amanullah (IIUM Press, 2022)
Islamic Sharīʽah includes all affairs of human life. An important part of Sharīʽah is related to human transactions. Conducting business is considered an important transaction, which has existed since the beginning of human life until today. Presently, committing unethical activities in conducting businesses has increased both among Muslims and non-Muslims all over the world. These unethical activities cause a Muslim to lose blessings of Allah Subḥānahū wa Taʽālā (SWT) in his income and make his earnings haram, which leads to unacceptance of his worship by Allah (SWT). It also causes harm to other people. This ultimately will be an important reason for him to be not successful on the Day of Judgment. To make a Muslim successful in this world and the life hereafter, Islam provides rules and guidelines to be followed. Among them are the rules and guidelines for conducting businesses sincerely and righteously. These rules and guidelines are called Islamic ethics of business. These ethics can be divided into two types: first, some attributes which must be possessed by a businessman; second, several forbidden things which must be avoided by him. This paper aims to analytically discuss the second type of these ethics and strives to investigate how committing these forbidden things causes to violate different types of maqāṣid (objectives) of Sharīʽah. An important finding of this research paper is that Islamic ethics of business have been prescribed by Allah (SWT) in a way that they maintain significant balance between dīn and dunyā and cause a Muslim to be successful both in this world and the next world.